Do terrorists get the attention they want?: comparing effects of terrorism across Europe - Nussio, Enzo (The public opinion quarterly, 2021)
Terrorists aim at influencing audiences beyond their immediate victims, but can only achieve this if an attack receives sufficient public attention. Previous research shows that terrorism can affect public opinion, but these studies are mainly based on emblematic single cases and relate to varying measures of influence, which are difficult to compare. This research focuses on the first-order effect of terrorism: attention. To analyze whether terrorists get attention, we combine a quasi-experimental approach for causal identification with a comparative design. We compile data from Eurobarometer surveys and contrast responses of more than 80,000 individuals surveyed before and after five diverse Islamist attacks in Europe in 2013-2019. Attention to terrorism increases in all targeted countries, regardless of attack size. Yet, while all incidents raise attention to terrorism, only larger attacks exert a meaningful impact across Europe.